2003
DOI: 10.1029/2001jc001194
|View full text |Cite
|
Sign up to set email alerts
|

Structure and eastward extension of the Changjiang River plume in the East China Sea

Abstract: The hydrographic structure and offshore extension of freshwater plume discharged from the Changjiang (also known as the Yangtze) River in the northern East China Sea were investigated by analyzing conductivity‐temperature‐depth (CTD) data and drifter trajectories collected during the summers of 1997 and 1998. From June to early September, when southerly winds prevail, the plume tends to move northeast in the Chinese coastal area and then separates from the coastal zone to travel eastward over 400 km offshore a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
153
0
5

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 11 publications
17
153
0
5
Order By: Relevance
“…During summer, the Changjiang Diluted Water (CDW) flows predominantly eastward (Lie et al, 2003). Therefore, the CJ transect (see Fig.…”
Section: Offshore Transect Along Cj Plumementioning
confidence: 99%
“…During summer, the Changjiang Diluted Water (CDW) flows predominantly eastward (Lie et al, 2003). Therefore, the CJ transect (see Fig.…”
Section: Offshore Transect Along Cj Plumementioning
confidence: 99%
“…It is a major source of freshwater on the ECS shelf and supplies about 90% of the total discharge of freshwater from rivers around the ECS and the Yellow Sea (Beardsley et al 1985;Zhang 1996). Freshwater from the Changjiang discharged into the ECS usually mixes with warm, saline waters (the Taiwan Warm Current and the Kuroshio and its branch currents, which flow northeastward over the outer shelf) to form a low salinity water mass called the Changjiangdiluted water (CDW) (Beardsley et al 1985;Ichikawa and Beardsley 2002;Lie et al 2003). The CDW generally has a sea-surface salinity (SSS) value less than 31 or 32 on the ECS shelf (Chang and Isobe 2003;Chen et al 2009;Moon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The motion of freshwater was also observed using satellite-tracked floats (Lie et al 2003). They found that some floats deployed near the river mouth (at 31.5°N) traveled northward in the shallow coastal region and then traveled northeast toward the west coast of Jeju Island in the shelf region (see their Fig.…”
Section: Response To Wind In 1996mentioning
confidence: 91%
“…The river discharge is the third largest in the world and the river contributes high levels of nutrients and organic matter to the ECS. The discharge forms a plume of Changjiang diluted water (CDW) by mixing with saline ambient water (Lie et al 2003).…”
Section: Introductionmentioning
confidence: 99%